Rancang Bangun Sistem Informasi Akademik Sekolah Berbasis Web Menggunakan Metode Prototyping Pada SMK Darma Nusantara - Ubadi Iskandar; Roy Mubarok (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This study aims to create a Web-Based School Academic Information System in a vocational high school. This research was conducted by conducting a field survey (school location) first through interviews and documentation. The results of the field survey found that the school did not have an adequate Academic Information System. All information system activities related to the academic process still use recording, storing academic data such as teacher, student data, grades and attendance data are still in the form of archives, making it difficult to find data. Therefore, the author wants to provide a web-based data processing solution to facilitate the school in processing the required academic data. The system is a Web-Based Academic Information System. This system is made using the PHP programming language and MySQL as its database server. Testing this system is done with a black box system and white box testing. The final result expected in this research is a website-based application that can facilitate work and search for academic data in schools.